2021
DOI: 10.1002/biot.202100570
|View full text |Cite
|
Sign up to set email alerts
|

Advancements in nucleic acids‐based techniques for bone regeneration

Abstract: The dynamic biology of bone involving an enormous magnitude of cellular interactions and signaling transduction provides ample biomolecular targets, which can be enhanced or repressed to mediate a rapid regeneration of the impaired bone tissue. The delivery of nucleic acids such as DNA and RNA can enhance the expression of osteogenic proteins. Members of the RNA interference pathway such as miRNA and siRNA can repress negative osteoblast differentiation regulators. Advances in nanomaterials have provided resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 97 publications
0
0
0
Order By: Relevance
“…RNA therapy first received attention in 1978 . RNA-based therapy for osteogenesis research primarily focuses on enhancing RNA transfection efficiency by combining RNA with bone tissue engineering carriers. RNA is loaded into scaffolds or administered systemically to transport it to the injury site, where it exerts its genetic function, thereby promoting osteogenesis. , Recent studies have revealed that extracellular nucleic acids can contribute to atherosclerosis by exerting their polyanionic properties . Pathological mineral deposits can be observed in atherosclerotic plaques, and histological studies have found that these ectopic calcification areas contain abundant deposits of calcium phosphate minerals .…”
Section: Introductionmentioning
confidence: 99%
“…RNA therapy first received attention in 1978 . RNA-based therapy for osteogenesis research primarily focuses on enhancing RNA transfection efficiency by combining RNA with bone tissue engineering carriers. RNA is loaded into scaffolds or administered systemically to transport it to the injury site, where it exerts its genetic function, thereby promoting osteogenesis. , Recent studies have revealed that extracellular nucleic acids can contribute to atherosclerosis by exerting their polyanionic properties . Pathological mineral deposits can be observed in atherosclerotic plaques, and histological studies have found that these ectopic calcification areas contain abundant deposits of calcium phosphate minerals .…”
Section: Introductionmentioning
confidence: 99%